Improvement of Erectile Dysfunction after Kidney Transplantation: the Role of the Associated Factors - Mehrsai, Abdolrasoul; Mousavi, Shahram; Nikoobakht, Mohammadreza; Khanlarpoor, Tina; Shekarpour, Leila; Pourmand, Gholamreza (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:"2 Mitra"; mso-font-alt:"Courier New"; mso-font-charset:178; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:8193 0 0 0 64 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate erectile dysfunction (ED) in hemodialysis patients and the factors influencing ED after a successful kidney transplantation. Materials and Methods: A total of 64 patients on hemodialysis were evaluated before and 6 months after the kidney transplantation. They were all recipients of their first kidney allografts from living unrelated donors and had a functional kidney allograft during the follow-up. The 5-item version of the International Index of Erectile Function (IIEF-5) was used to assess their erectile function. A group of age-matched controls were compared with them before transplantation. The effects of pretransplant IIEF-5 score, age at transplantation, the artery used for anastomosis, and duration of the dialysis prior to transplantation on ED were also studied. Results: Fifty-six of the patients (87.5%) and 23 of the controls (35.9%) had ED (P < .001). The prevalence of ED was 87.5% in the hemodialysis patients. There was no relationship between the duration of dialysis and the severity of ED. Successful transplantation improved IIEF-5 score significantly (13.6 ± 5.2 before and 19.2 ± 5.0 after transplantation; P < .001). Based on the IIEF-5 scores, the severity of ED increased in 6 (9.4%) patients; 8 (12.5%) experienced no change in their erectile function; and 50 (78.1%) reported an improved erectile function. Preoperative IIEF-5 score and age at transplantation had statistically significant associations with ED improvement (P < .001; P = .02). Conclusion: Erectile dysfunction is highly prevalent in hemodialysis patients and significantly improves after successful kidney transplantation. Younger patients with a less severe ED have the most improvement after transplantation.